2021
DOI: 10.1111/jace.17852
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence against the alleged failure of the classical nucleation theory below the glass transition range

Abstract: We collected a plethora of new data to test the hypothesis that the failure of the Classical Nucleation Theory (CNT) below the glass transition range is just an experimental artifact. Since reaching the steady‐state nucleation regime takes a significant time for treatments below the glass transition temperature, data collected in this temperature range tend not to have reached a steady state. Because of this potential problem, we examined the CNT using new experimental data for three stoichiometric silicate gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The temperature dependence (450°C–600°C) of r * and Δ G * in Li 2 O–2SiO 2 glass/SCL is shown in Figure 8, indicating that both parameters increase with increasing temperature. That is, for the formation of nanocrystals having radius as possible as small, the nucleation should be carried out at low temperatures close to the glass transition temperature, that is, T g = 455°C 16 …”
Section: Scientific Background Behind Nucleation and Nanocrystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature dependence (450°C–600°C) of r * and Δ G * in Li 2 O–2SiO 2 glass/SCL is shown in Figure 8, indicating that both parameters increase with increasing temperature. That is, for the formation of nanocrystals having radius as possible as small, the nucleation should be carried out at low temperatures close to the glass transition temperature, that is, T g = 455°C 16 …”
Section: Scientific Background Behind Nucleation and Nanocrystallizationmentioning
confidence: 99%
“…Numerous studies on the nucleation mechanism and kinetics in oxide SCLs have been reported so far. In particular, the homogeneous nucleation kinetics by thermodynamic approach based on the classical nucleation theory (CNT) for some stoichiometric SiO 2 ‐based glasses/SCLs such as lithium disilicate Li 2 O–2SiO 2 and Na 2 O–2CaO–3SiO 2 have been studied in detail 4,11–16 . In the CNT approach, one of the most crucial issues is to evaluate the interfacial energy ( γ ) at the SCL–nucleus interface, because the γ value itself in oxide glasses/SCLs has not been measured directly (independently) from experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, recent works are proposing a new theory to study nucleation, relating the relaxation of the material with the time needed to reach steady‐state nucleation, where it is proposed that a glass will only reach its steady state corresponding to the fully relaxed supercool liquid state 14–19 . Crystal nucleation happens concomitantly with the relaxation process toward the SCL, strongly affecting the nucleation rate measured at temperatures below T max , taking a very long time to reach steady‐state nucleation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…12 Lastly, recent works are proposing a new theory to study nucleation, relating the relaxation of the material with the time needed to reach steady-state nucleation, where it is proposed that a glass will only reach its steady state corresponding to the fully relaxed supercool liquid state. [14][15][16][17][18][19] Crystal nucleation happens concomitantly with the relaxation process toward the SCL, strongly affecting the nucleation rate measured at temperatures below T max , taking a very long time to reach steady-state nucleation. 15 Finally, on a similar note, Abyzov et al showed that stresses present in the material reduce the thermodynamic driving force for crystallization and thus increase the nucleation barrier, causing a decrease in the nucleation rate.…”
Section: Introductionmentioning
confidence: 99%
“…However, the complicated structure of the textile usually hinders the distribution of the fillers into/onto the fabric. Neither the classical melting mixing method , nor the in situ process for producing conductive composites is applicable for strain sensors based on textile matrices. Therefore, dip-coating processes with chemical solvents are often used. , …”
Section: Introductionmentioning
confidence: 99%